Residuos y paradojas en la diacronía de los adverbios en -mente. Evidencia para la gramaticalización - Company Company, Concepción (El Colegio de México, 2014)
This paper deals with historical syntax and grammaticalization. The paperintroduces two new theoretical concepts in grammaticalization: residue andparadox. Residue is understood like a non-productive form in the language,paradox, as a contradiction or an unexpected structure or linguistic situation.These two concepts may shed light on which areas of grammar are promptedto grammaticalize. The paper firstly sums up the basic aspects of grammaticalizationand lists six kinds of residues and paradoxes. Secondly, the article analyzesthe evolution of Spanish manner adverbs in -mente, because they exhibita big paradox: to be a paradigmatic grammaticalization and to be a non-endedgrammaticalization simultaneously. Finally, the paper analyzes a sorpressiveresidue in the diachrony of these adverbs; the disappearance and reappearanceof the noun mente in Spanish, showing that stratification possibly is not adefinitely feature of grammaticalization.